1981
DOI: 10.1111/j.1600-051x.1981.tb00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between periodontal disease and cirrhosis of the liver in humans

Abstract: The periodontal condition of a well-described group of cirrhotic patients was compared with that of a control group, matched for age, sex ratio and socio-economic background, expressed as years of education. The test group comprised 30 cirrhotic patients, 35-64 years of age. The diagnosis cirrhosis of the liver was confirmed histologically, and no other systemic diseases were present. The material was grouped according to age, 35-44, 45-54 and 55-64 years of age. The examination included determination of tooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 15 publications
3
38
0
1
Order By: Relevance
“…Further, observational studies have confirmed these findings (Aberg et al, ; Alazawi et al, ; Di Profio et al, ; Jaiswa et al, ; Lins et al, ; Oettinger‐Barak et al, ; Raghava et al, ). However, other studies failed to report this association (Guggenheime et al, ; Movin, ; Novacek et al, ). Frequent potential biases can be observed in several studies such as the use of retrospective data obtained from medical records, indexes or radiograph exams for characterizing periodontitis, small samples, self‐reported information on periodontal and cirrhosis conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, observational studies have confirmed these findings (Aberg et al, ; Alazawi et al, ; Di Profio et al, ; Jaiswa et al, ; Lins et al, ; Oettinger‐Barak et al, ; Raghava et al, ). However, other studies failed to report this association (Guggenheime et al, ; Movin, ; Novacek et al, ). Frequent potential biases can be observed in several studies such as the use of retrospective data obtained from medical records, indexes or radiograph exams for characterizing periodontitis, small samples, self‐reported information on periodontal and cirrhosis conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have addressed the relationship between periodontal disease and liver cirrhosis (Grønkjaer, 2015). While studies reported a higher rate of periodontitis among cirrhotic individuals when compared to controls (Åberg, Helenius-Hietala, Meurman, & Isoniemi, 2014;Alazawi et al, 2017;Di Profio et al, 2018;Grønkjaer,et al, 2018;Jaiswal, Deo, Bhongade, & Jaiswal, 2011;Lins et al, 2011;Oettinger-Barak et al, 2001;Raghava, Shivananda, Mundinamane, Boloor, & Thomas, 2013), others failed to indorse this finding (Guggenheimer, Eghtesad, Close, Shay, & Fung, 2007;Movin, 1981;Novacek et al, 1995). Additionally, other cirrhotic outcomes have been linked to periodontitis and include the progression of liver disease, accelerated Model for End-Stage Liver Disease (MELD) scores (Åberg et al, 2014) and the presence of systemic infections (Lins et al, 2011).…”
Section: Studies Have Indicated An Association Between Periodontitismentioning
confidence: 99%
“…The numbers of cases among those reporting recent alcohol intake of 0.1-4.9 g/day were 550; 5.0-14.9 g/day, 562; 15-29.9 g/day, 276; for > 30 g/day, 288; and for non-drinkers, 449. intake and periodontitis. Early studies observed increased prevalence and severity of periodontal disease among patients with cirrhosis (Sandler and Stahl, 1960;Movin, 1981), and attributed this to poor oral hygiene (Movin, 1981). Other studies reported worse periodontal conditions in alcoholic patients with and without cirrhosis than in healthy subjects (Dunkley and Carson, 1968;Novacek et al, 1995) and in nonalcoholic patients with cirrhosis (Novacek et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the past decade have suggested a positive association between high alcohol consumption and periodontitis (Sakki et al 1995, Tezal et al 2001, 2004, Pitiphat et al 2003, Shimazaki et al 2005, Okamoto et al 2006, Jansson 2008. Also, studies have related alcohol abuse (Harris et al 1997) and alcohol-induced hepatic cirrhosis (Movin 1981, Novacek et al 1995 to periodontal status. However, the studies differed according to the definition of periodontitis and results were diverse.…”
mentioning
confidence: 99%